Flexural behaviour of RC beams strengthened with wire mesh-epoxy composite - Qeshta, I.M.I.; Shafigh, P.; Jumaat, Mohd Zamin (Elsevier, 2015)
In this research work, the flexural behaviour of reinforced concrete (RC) beams strengthened with a new type of strengthening material, namely wire mesh-epoxy composite, was investigated. The flexural behaviour of RC beams strengthened using this new material was compared with RC beams strengthened with carbon fibre reinforced polymer (CFRP) sheet. In addition, the structural performance of a beam strengthened using a hybrid of wire mesh-epoxy and CFRP sheet was investigated. The results showed that the use of wire mesh-epoxy composite provides considerable enhancement in the performance of strengthened beams. Compared to CFRP, the wire mesh-epoxy strengthened beams showed more improvement in the first crack load, stiffness and yield strength. In addition, the use of hybrid wire mesh-epoxy-carbon fibre composite indicated better post-yield behaviour and prevented the debonding of the CFRP sheet. (C) 2015 Elsevier Ltd. All rights reserved.